Kinerja Pegawai terhadap Kepuasan Masyarakat dalam Pelayanan Publik Berbasis Digital di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bantul - Susatyo Herlambang; Christantra Yoga Grahito Hutomo; Muhammad Isnaini Fathoni (Jurnal Bisnis Administrasi dan Manajemen, 2026)
Digital transformation in public services requires government institutions to improve service quality by leveraging information technology. However, the success of public services is determined not only by digital systems but also by employee performance as service providers. This study aims to analyze the effect of employee performance on community satisfaction in digital-based population administration services at the Department of Population and Civil Registration of Bantul Regency. A quantitative approach with an associative design was employed. The sample consisted of 86 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using simple linear regression. The findings indicate that employee performance positively influences community satisfaction. The results highlight the important role of human resource quality in supporting successful digital-based population administration services. This study provides empirical contributions to public administration literature and practical insights for improving public service quality.